Factors affecting auditor performance: Information technology, Auditor experience and Professional skepticism (Review Literature) - Kusmanto, Diana; Nugrahanti, Trinandari Prasetya (Westscience Press, 2025)
Auditor performance is influenced by various factors that can determine the effectiveness and efficiency of the audit process. The three main factors that are the focus in this study are auditor performance, especially in the context of information technology, auditor experience, and professional skepticism The application of sophisticated information technology enables auditors to access data more quickly and accurately, as well as improve their analytical skills, auditor experience contributes significantly to understanding and skills in identifying risks and making the right decisions in audits. High professional skepticism encourages auditors to question the information presented and consider the possibility of errors or fraud. This methodology uses a literature review approach using a database from Google Scholar and previous research to collect information and publications in the last two years. This study aims to explore the interaction of information technology, auditor experience and professional sectism on auditor performance, and the results of this research can provide in-depth insights on how to improve audit quality. This research is expected to be a reference for better auditing practices and professional development in the future.